Peran Divisi IV Angkatan Laut dalam Mempertahankan Kemerdekaan Indonesia di Kalimantan Selatan, 1946-1950 - Fajar Firdaus; Abd Rahman Hamid; Uswatun Hasanah (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
This article discusses the role of the Fourth Division of the Indonesian Navy in maintaining Indonesian independence during the physical revolution (1945–1949), particularly in the South Kalimantan region. The writing uses historical methods that include heuristic stages, source criticism, interpretation, and historiography to construct a structured national historical narrative. The results of the study show that the Indonesian Navy made significant contributions through naval operations, resistance coordination, and efforts to secure Kalimantan's territorial waters. Despite facing limited weaponry and a Dutch naval blockade, the Fourth Division of the Indonesian Navy was still able to carry out its role as a maritime defense fortress and a symbol of resistance against colonialism. The success of their operations not only maintained territorial integrity but also strengthened the de facto legitimacy of the Republic of Indonesia in the region. This study contributes to filling the gap in the history of the revolution in South Kalimantan with a maritime history approach.